4CPS-061 Antibiotic prophylaxis for preventing surgical wound infection after elective caesarean section: meta-analysis of clinical trials. (2nd March 2018) - Panciroli, C; Luoni, A; Bignamini, A; Minghetti, P
Abstract : Background: Surgical site infection (SSI) following caesarean section is the most important risk factor for postpartum morbidity, patient hospitalisation and its costs. Guidelines are recommended for the use of antibiotic prophylaxis for caesarean section to prevent wound infection. Moreover, increasing concerns about the emergence of resistant strains of common bacteria have resulted in increased scrutiny of the use of antibiotics during pregnancy, particularly in the hospital setting. Purpose: A systematic review focused on the effectiveness of antibiotic prophylaxis, to prevent SSI, in cohorts of low-risk females undergoing elective caesarean section. Material and methods: A systematic review of the literature was performed by searching in an electronic database (PubMed, Embase, etc.). All randomised controlled trials (RCTs) that evaluate the effects of antibiotic prophylaxis in elective caesarean section compared to placebo/no treatment were included. Subgroup analysis was carried out by the time of administration (before cord clamping, after, not defined) and by class of antibiotic. All statistical calculations were performed using Software R. The effect estimate was reported in risk ration (RR) and pooled using a random-effects model and the Mantel–Haenszel method. Results: The search identified 129 studies, 18 were included and 111 were excluded. The 18 studies that met the inclusion criteria enroller 4. 549 females total : 2106 patients treated and 1845 controls. The estimated total effect of the intervention, expressed as RR of ISS, was significant (RR 0.60; 95% CI: 0.42 to 0.84; p=0.003). There was no substantial heterogeneity among the studies (I2: 14.6%). Similar estimates of effect were seen in subgroup analysis of ISS by the timing of administration: before cordon clamping (RR 0.49; 95% CI: 0.19 to 1.26; p=0, 136); after cordon clamping (RR 0. 64; IC95% 0. 42–0. 99; p=0. 045); not defined time (RR 0. 22; 95% CI: 0.05 to 0.99; p=0.049). The effect of different classes of antibiotics could not be properly estimated, although the meta-analysis of the studies with beta-lactamase inibitor combinations yielded a statistically significant effect (RR 0.17; 95% CI: 0.06 to 0.49; p<0.001). Conclusion: This systematic review and meta-analysis supports the guidelines' recommendation: antibiotic prophylaxis should be regularly administered to all females undergoing elective caesarean section to prevent ISS. Similar estimates of effect were observed regarding the timing of administration, but there were insufficient data to compare antibiotic classes. No conflict of interest